1986
DOI: 10.1128/jb.166.3.945-958.1986
|View full text |Cite
|
Sign up to set email alerts
|

Autogenous regulation of the gene for transcription termination factor rho in Escherichia coli: localization and function of its attenuators

Abstract: We present evidence that the expression of rho is regulated by rho-dependent attenuation of transcription. Gene fusion analysis with nested series of deletions of rho indicated that the transcription of rho is attenuated in a rho-dependent manner in the leader region and that neither a read-through transcription from the upstream gene, trxA, nor a modulation of transcription initiation of the rho promoter is involved in the self-control of rho. Si mapping and Northern hybridization analyses localized at least … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
65
1

Year Published

1987
1987
2018
2018

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 88 publications
(71 citation statements)
references
References 54 publications
5
65
1
Order By: Relevance
“…In contrast, we observed that bicyclomycin had a strong effect on the level of rho mRNA (SI Appendix, Fig. S5), which is known to be autoregulated via a Rho-dependent mechanism (20). Therefore, our results show that the level of the lysC mRNA is not controlled via a Rho-dependent transcription regulation mechanism.…”
Section: Level Of Lysc Mrna Decreases Rapidly In the Presence Of Lysinecontrasting
confidence: 53%
“…In contrast, we observed that bicyclomycin had a strong effect on the level of rho mRNA (SI Appendix, Fig. S5), which is known to be autoregulated via a Rho-dependent mechanism (20). Therefore, our results show that the level of the lysC mRNA is not controlled via a Rho-dependent transcription regulation mechanism.…”
Section: Level Of Lysc Mrna Decreases Rapidly In the Presence Of Lysinecontrasting
confidence: 53%
“…Results of previous studies suggest that expression of Salmonella adherence and invasion factors is induced by the low oxygen environment of the intestinal lumen (13)(14)(15) obtain rare transposon mutations that affect the expression of rho, an essential bacterial gene, by insertion in the 300 base pairs that comprise the promoter of rho (28,31). Only three genetic loci were identified that result in increased aerobic invasiveness.…”
Section: Resultsmentioning
confidence: 99%
“…In view of the binding of YaeO to Rho, the requirement for a strong expression is not surprising as Rho is abundant (approximately 0.3% of total proteins), and autoregulation of rho (Blumenthal et al, 1976;Brown et al, 1982;Matsumoto et al, 1986), as illustrated in Fig. 5, may further dampen the effects of YaeO.…”
Section: Discussionmentioning
confidence: 99%
“…was analysed. It is known that the rho gene is autoregulated by termination in the leader region of the gene by t rho (Brown et al, 1982;Tsurushita et al, 1984;Matsumoto et al, 1986). We tested the inhibition of Rho function by measuring the expression of gene rho in a pSC101-derived plasmid in which most of the rho coding region was replaced by lacZ (Fig.…”
Section: Fig 3 Sds-page Of Ni 2þmentioning
confidence: 99%
See 1 more Smart Citation